DORSAL PANCREATIC AGENESIS PRESENTING AS NEW-ONSET TYPE 3C DIABETES IN A YOUNG MALAYSIAN ADULT: A CASE REPORT - Ismail , Ihsan; Zuki, Rabeah Md (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Type 3C diabetes mellitus (DM), secondary to exocrine pancreatic disease, is uncommon. Dorsal pancreatic agenesis (DPA), a rare congenital absence of part of the pancreas, can lead to both exocrine insufficiency and DM. We present a unique case of new-onset Type 3C DM due to DPA in a young Malaysian adult. CASE A 26-year-old Malaysian male with no known medical illness presented with a 6-month history of worsening loose stools, significant 15 kg weight loss, increased hunger, foot numbness, and blurred vision. His initial blood glucose was very high (58.7 mmol/L), leading to a diagnosis of new-onset DM. However, his weight loss and diarrhea were atypical. Tests for viral hepatitis, HIV, and diabetes autoantibodies were negative. Colonoscopy was normal. A CT scan of the abdomen revealed findings suggestive of DPA. Consequently, a diagnosis of Type 3C DM secondary to DPA and likely exocrine pancreatic insufficiency-related diarrhea was made. He was started on insulin, and his gastrointestinal symptoms improved moderately with diet and lifestyle changes. DPA is a rare cause of DM, especially in young adults. The absence of typical autoimmune markers and the presence of significant exocrine symptoms were key in identifying this unusual etiology. The development of diabetes in DPA is thought to be due to reduced pancreatic beta-cell mass. This case highlights the importance of considering rare causes like DPA in atypical diabetes presentations. Thorough evaluation, including imaging, is crucial for accurate diagnosis and management. While insulin therapy was initiated, dietary modifications provided some relief for his gastrointestinal issues. CONCLUSION This case demonstrates a rare instance of Type 3C DM secondary to DPA in a young Malaysian adult. It emphasizes the need for awareness of such unusual associations in young patients with new-onset diabetes and unexplained gastrointestinal symptoms. Further research on DPA-related diabetes in Malaysia is warranted.